(untitled) (Iranian Journal of Kidney Diseases, 2016)
Introduction. Protein-energy wasting (PEW) is very common in patients with chronic kidney disease and those undergoing maintenance dialysis. Reduced handgrip strength is associated with PEW and considered as a reliable nutritional parameter that reflects loss of muscle mass. This study aimed to evaluate the handgrip strength and its relationship with the Malnutrition-Inflammation Score (MIS) among Iranian dialysis patients. Materials and Methods. The study population consisted of 83 randomly selected hemodialysis patients from the dialysis centers in Kerman, Iran. Handgrip strength was measured using a dynamometer according to the recommendations of the American Society of Hand Therapists. All the patients were interviewed and the MIS of the patients were recorded. Results. The PEW was prevalent in Kerman hemodialysis patients, with 83% and 17% having mild and moderate PEW based on MIS, respectively. Handgrip strength was significantly associated with age, sex, height, weight, and diabetes mellitus. After adjustment for age, handgrip strength was significantly associated with nutritional assessment markers on the basis of the MIS. Conclusions. Handgrip strength can be incorporated as a reliable tool for assessing nutrition status in clinical practice. However, further research is needed to determine the reference values and cutoff points both in healthy people and in hemodialysis patients to classify muscle wasting.